Continuous maintenance and enhancement of the quality management systems (QMS) at the Faculty of Pharmacy, UiTM through internal audit - Lim, Siong Meng (Faculty of Pharmacy, 2026)
This year, the Faculty of Pharmacy, UiTM has seen two newest additions to the internal audit team led by Assoc. Prof. Dr.Lim Siong Meng. The timely appointment of the two new internal auditors, namely Assoc. Prof. Dr. Yuslina Zakaria and Mdm.Nur Syazwani Taridi, is necessary to strengthen the team of nine other internal auditors (i.e., Dr. Norazlina Ahmad, Dr.Mashani Mohamad, Assoc. Prof. Dr.Mahmathi Karuppannan, Assoc. Prof. Dr.Nurul Aqmar Mohamad Nor Hazalin, Dr.Aisyah Hasyila Jahidin, Prof. Dr. Mizaton Hazizul Hasan, Mdm. Tiniati Ahmad, Mr.Mohamad Rahimi Sulaiman, and Mr. Fairos Abdul Hamid).